Immunological control of ticks and tick-borne parasitic diseases of livestock - Morrison, W. Ivan (Cambridge University Press, 1989)
Parasitic diseases inflict major losses on livestock production throughout the world. Currently, control of the diseases relies largely on prophylactic or therapeutic application of anti-parasitic drugs. In many instances, these measures are only partially effective. Moreover, they must be applied frequently, are therefore costly and time-consuming, and lead to the selection of drug resistance within the parasite populations. Thus, it has been recognized for several decades that effective methods of vaccination against parasitic diseases would have a major impact on livestock production. However, despite considerable efforts over the last 30 years, only a few parasite vaccines are currently in use and all of these involve the administration of live organisms.